Life et la politique d’endiguement ou la photographie de presse comme outil de propagande - Jane Bayly-Colin Heather (Amnis)
The power of the emotional impact of the image is undeniable, but when it accompanies text, or even entirely replaces it, as in the case of Life magazine, and becomes the primary source of information, how does it influence the understanding of the news? Week after week, Life provided its readers a large selection of images that offered them greater depth of knowledge about topics ranging from the news, history and science to fashion and the arts. However, the magazine did not just entertain and inform, it transmitted a partial view of America and the world. The aim of this article is to demonstrate how, during the second half of the 1940s, Life’s photography transmitted nationalist propaganda for the politic of containment.